A Pengembangan Soal Berbasis Problem Based Learning (PBL) Sebagai Pengukur Kemampuan Berpikir Kritis dan Analitis Siswa Pada Materi Sistem Ekskresi Manusia di SMPN 7 Mempawah Hulu - Sari, Mustika; Nova Cantika; Eka Trisianawati (Program Studi Pendidikan Fisika, Fakultas Pendidikan MIPA & Teknologi, Universitas PGRI Pontianak, 2024)
This study aims to develop Problem Based Learning (PBL) based questions to measure students critical and analytical thinking skills that are valid, practical, and effective. This research method uses research and development (Research and Development) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Indirect communication, and measurement data collection techniques. Data collection tools used validation sheets, questionnaires and tests. The research subjects were class IX SMP Negeri 7 Mempawah Hulu. Data analysis techniques validity and practicality based on questionnaire sheets and Likert scale, while effectiveness based on data from the results of Problem Based Learning questions developed. The results of this study showed that: 1) product validity based on material experts obtained 92.8% very valid category and based on media experts obtained 96.8% very valid category 2) calculation of practicality level obtained 80% practical category 3) calculation of effectiveness level obtained 82% with very effective category. Conclusion: Problem Based Learning (PBL) based questions are classified as valid, practical and effective for use in the learning process as a measure of students' critical and analytical thinking skills.